(1+i)*z*z+2iz-1=0

Simple and best practice solution for (1+i)*z*z+2iz-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1+i)*z*z+2iz-1=0 equation:


Simplifying
(1 + i) * z * z + 2iz + -1 = 0

Reorder the terms for easier multiplication:
z * z(1 + i) + 2iz + -1 = 0

Multiply z * z
z2(1 + i) + 2iz + -1 = 0
(1 * z2 + i * z2) + 2iz + -1 = 0

Reorder the terms:
(iz2 + 1z2) + 2iz + -1 = 0
(iz2 + 1z2) + 2iz + -1 = 0

Reorder the terms:
-1 + 2iz + iz2 + 1z2 = 0

Solving
-1 + 2iz + iz2 + 1z2 = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 2iz + iz2 + 1 + 1z2 = 0 + 1

Reorder the terms:
-1 + 1 + 2iz + iz2 + 1z2 = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 2iz + iz2 + 1z2 = 0 + 1
2iz + iz2 + 1z2 = 0 + 1

Combine like terms: 0 + 1 = 1
2iz + iz2 + 1z2 = 1

Add '-1z2' to each side of the equation.
2iz + iz2 + 1z2 + -1z2 = 1 + -1z2

Combine like terms: 1z2 + -1z2 = 0
2iz + iz2 + 0 = 1 + -1z2
2iz + iz2 = 1 + -1z2

Reorder the terms:
-1 + 2iz + iz2 + z2 = 1 + -1z2 + -1 + z2

Reorder the terms:
-1 + 2iz + iz2 + z2 = 1 + -1 + -1z2 + z2

Combine like terms: 1 + -1 = 0
-1 + 2iz + iz2 + z2 = 0 + -1z2 + z2
-1 + 2iz + iz2 + z2 = -1z2 + z2

Combine like terms: -1z2 + z2 = 0
-1 + 2iz + iz2 + z2 = 0

The solution to this equation could not be determined.

See similar equations:

| 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= | | Y^2=5Y+50 | | 89=28-r | | 36=-3(-9-3z) | | 33x+117=14.5x | | 6x^3-4x-16x=0 | | 89=21-r | | 12=-8p+11+9p | | 1.5x+10=2x+20 | | 1216=(x*2140)/(7443,8*0,1) | | 2r^2-4=8 | | x^4+5x^2-6= | | -7x+17= |

Equations solver categories